Climate and land-use changes threaten the effectiveness of protected areas for protecting Galliformes in Southeast Asia - Liu, Zhengxiao; Tian, Shan; Lu, Shuai; Zhu, Ziqiang; Peng, Yuyang; Li, Xinyu; An, Lidan; Li, Jianqiang; Xu, Jiliang; Wang, Yong (Frontiers in Ecology and Evolution, 2023)
Climate and land-use changes and their interactions have a profound effect on biodiversity, especially in biodiverse areas such as Southeast Asia (SEA) where aggregations of endemic species are widespread. To increase the effectiveness of biodiversity protection, it is crucial to understand the effect of climate and land-use changes on biodiversity. In the present study, we predicted future land-use changes based on a Cellular automaton Markov chain model (CA-MARKOV), and took Galliformes species as an example to assess the impact of climate and land-use changes on the effectiveness of protected areas in SEA. In addition, we used an ensemble of species distribution models (SDMs) to assess the potential habitats and their dynamics of 62 Galliformes species currently and in the 2070s. Our results showed that climate and land-use changes would reduce the suitable habitats of these Galliformes species. Among them, 22 or 31 species would migrate upward because of a decrease in habitat suitability at lower elevations caused by climate and land-use changes, while other 40 or 30 species were predicted to migrate downward because of land use changes under two dispersal scenarios. Theses changes would expand the area with low and high diversity, but there would be a mismatch between the current protected areas (PAs) and future suitable habitats with high diversity. In order to effectively ensure biodiversity protection and conserve 30% of the planet by 2030, our findings suggest that we should establish new PAs or adjust the range of PAs based on the impact of climate and land-use changes.